A Job Club for Older Job Seekers: Change in Attitude and Perceived Utility During Training. (December 2018) - Nakai, Yoshie; Hill, Stephen C.; Snell, Andrea F.; Ferrell, Jared Z.
The purpose of the current study is to explore the changes in participants' attitude toward job search and perceived utility of training during job search interventions, called job clubs, designed for older adults. Latent growth modeling was used to examine the trajectories of these outcomes during 3-week-long job clubs. In addition, the study examined the relationship between participants' self-regulatory skills (emotion control and motivation control) and the training outcomes. In Study 1 (20 job clubs, N = 200) and Study 2 (36 job clubs, N = 385), participants showed continuous positive change in the attitude and perceived utility of training. Although self-regulatory skills in the beginning of job club were not related to the improvement in the outcomes, dynamic measures of emotion control predicted change in attitude and motivation control predicted both attitude and perceived utility of training.